How Do Neighborhood Attributes Relate to Life Satisfaction and Neighborhood Satisfaction Differently? - Xinyi Wu; Jason Cao; Yingling Fan; Anu Ramaswami (Findings)
Neighborhood attributes may have different relationships with neighborhood satisfaction and life satisfaction. However, few studies have compared linkages between the neighborhood environment and these two satisfaction outcomes. This study fills this gap by illustrating how the same neighborhood attributes relate to neighborhood satisfaction and life satisfaction differently. Results indicate that the neighborhood environment has a stronger association with neighborhood satisfaction than with life satisfaction. Moreover, attributes pertinent to neighborhood appearance and basic features have the strongest connection with neighborhood satisfaction, whereas attributes regarding leisure activities and social cohesion show more substantial correlations with life satisfaction than other neighborhood attributes.